Genetic surveillance and crime control: social, cultural, and political perspectives - Machado, Helena (2021)
[Excerpt] Introduction A striking aspect of 21st-century societies in the governance of crime is the growing role of scientific and technological innovations in the field of forensic genetics. The aim of forensic genetics is to identify individuals through the collection of their biological traces – blood, hair, saliva, or other fluids. The possibility of deriving DNA (a biological structure considered unique to each individual) from biological matter – whether inadvertently left behind by criminal suspects at crime scenes or directly obtained from the bodies of criminal suspects − has contributed decisively in predisposing governments to support the developments and ambitions of forensic genetics.